Intersection of exogenous, endogenous and anthropogenic factors in the Holocene landscape: A study of the Naples coastline during the last 6000 years - Romano, P.; Di Vito, M.A.; Giampaola, D.; Cinque, A.; Bartoli, C.; Boenzi, G.; Detta, F.; Di Marco, M.; Giglio, M.; Iodice, S.; Liuzza, V.; Ruello, M.R.; et al. (Quaternary international, 2013)
New data on the ancient landscape of Naples (southern Italy) during the middle and late Holocene from geo-archaeological excavations associated with public transport works were used to reconstruct the hill and coastal environment to the west of the ancient Graeco-Roman polis, where remains of human settlements date to the late Neolithic. The rich stratigraphic and archaeological records that emerged from the digs and from previous boreholes were measured and analysed by combining sedimentary facies analysis, tephrostratigraphy and archaeological data. Between the 5th and 4th millennia BP, a rocky profile with a wave-cut platform cutting across pyroclastites emplaced from the surrounding volcanoes was predominant in the coastal landscape. During the 3rd millennium BP, this rocky coast was progressively replaced by a sandy littoral environment primarily due to marine deposition, with a coastline located some hundred meters inland with respect to the modern one. The sedimentary record of the Greek and Roman periods indicates short-term fluctuations of the coastline, leading to the establishment of a backshore environment towards the end of the 6th century AD, when prograding river mouths and lobes of debris flows contributed to the advancing trend of the shoreline. The frequent archaeological remains from these periods indicate a stable settled area since Roman times. The shoreline was still subject to short-lived fluctuations between the 12th and 16th centuries, and attained its present position during the modern era with man-made reshaping of its profile. The construction of Relative Sea Level curves for two coastal sites reveals that the persistence of the foreshore environment in the Naples coastal strip during the 5th and 4th millennia BP was controlled by the counterbalancing effect of either the concurrent eustatic sea level rise or subsidence. On the other hand, the morpho-stratigraphic record for the last two millennia shows a significant correlation between sedimentation rate and settlement history, accounting for the dominant role of the anthropogenic forcing-factor in late Holocene landscape history. In particular, land mismanagement during Late Antiquity seems to have triggered a slope disequilibrium phase, exacerbating soil erosion and increasing the sediment accumulation rate in both foothill and coastal areas. Nonetheless, the environmental changes of the Chiaia coast during the last 2000 years clearly show volcanic–tectonic perturbations influencing coastline development up to the modern era.